2012
DOI: 10.1007/s10195-012-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the rotation center of the hip after oblong cups in revision total hip arthroplasty

Abstract: BackgroundThe preoperative bone defect and the reconstruction of the center of rotation of the hip are critical in acetabular revision surgery. Uncemented oblong cups are employed in order to manage these issues. We analyzed the clinical results and rates of revision of two different uncemented oblong cups, the reconstruction of the center of rotation of the hip, as well as the rate of radiological loosening and possible risk factors.Materials and methodsForty-five patients (46 hips) underwent acetabular revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Advantages of un uncemented hemispherical cup are a stable and biologic fixation in mild-to-moderate bone defects and a surgical technique familiar to many arthroplasty surgeons; however, it is accepted that provide poor results in severe acetabular bone defects (>50% of bone stock). 51 …”
Section: Reconstruction Available Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advantages of un uncemented hemispherical cup are a stable and biologic fixation in mild-to-moderate bone defects and a surgical technique familiar to many arthroplasty surgeons; however, it is accepted that provide poor results in severe acetabular bone defects (>50% of bone stock). 51 …”
Section: Reconstruction Available Optionsmentioning
confidence: 99%
“… 55 , 56 Oblongs cups adapt better to large and oblong bone defects, that cannot be filled with hemispherical cups, avoiding marked reaming of the anterior and posterior columns. 51 , 55-61 Three types of Oblong Cups have been described: the bilobed oblong acetabular component, the longitudinal oblong revision cup (LOR) and the BOFOR cup. 56 In a recent systematic review, Volpin et al , 11 reported good results for oblong cups in term of overall failure rate (5.9%, 12 of 203 hips) with an aseptic loosening rate of 3.9% (8 of 203 hips) and a dislocation rate of 2.4% (5 of 203 hips) at a mean follow-up of 7.6 years.…”
Section: Reconstruction Available Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oblong uncemented cups are an option for revision surgery, but care must be taken in major acetabular bone defects. Cup stability is one of the concerns in different series, although acetabular reconstruction close to the approximate true centre of the femoral head may improve clinical results (9).…”
Section: Classification Of Acetabular Defectsmentioning
confidence: 99%
“…Hierbei überbrückt der Ring den knöchernen Defekt, schützt eine defektfüllende Knochenplastik und ermöglicht somit deren Umbau in nativen Knochen[30]. In einer Studie an 50 azetabulären Revisionen mit allogenen, vorwiegend strukturellen Transplantaten, die durch einen Ring geschützt waren und bei denen eine spätere Revision notwendig wurde, berichteten die Autoren über eine Transplantatintegration in 31 Fäl-Die Präparation des Implantatlagers ist als eher schwierig einzustufen, besonders zu achten ist auf den Erhalt des mechanisch tragenden autochthonen Restknochens während der Präparation, um eine stabile Implantatfixierung zu erreichen[35,36]. Es liegen derzeit wenige Ergebnisse mit eher inhomogener Überlebensrate vor.…”
unclassified